2019
DOI: 10.3889/oamjms.2019.059
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Hyaluronic Acid Microinjection for Skin Rejuvenation in Vietnam

Abstract: BACKGROUND:Aging is an increasing concern of modern society, particularly facial ageing. In recent years, the microinjection technique has increasingly been emphasised as a skin rejuvenation strategy. Hyaluronic acid (HA) plays an important role in the hydration of the extracellular space and can thus improve skin hydration, firmness and viscoelastic properties.AIM:To evaluate the efficacy and safety of HA microinjection in skin rejuvenation.METHODS:We enrolled thirty participants underwent three sessions of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…HA filler injections used to enhance lip fullness indicated that HA is safe and effective (17). Consistent with these results, 93% of participants in the HA face microinjection procedure felt satisfied with no remarkable adverse effects (18). HA dermal fillers have evolved in recent years, and some complications have been associated with their use.…”
Section: Introductionsupporting
confidence: 53%
“…HA filler injections used to enhance lip fullness indicated that HA is safe and effective (17). Consistent with these results, 93% of participants in the HA face microinjection procedure felt satisfied with no remarkable adverse effects (18). HA dermal fillers have evolved in recent years, and some complications have been associated with their use.…”
Section: Introductionsupporting
confidence: 53%
“…A high level of satisfaction with the appearance of the facial skin after tear trough and temporal fossa augmentation was noted by Tung et al, and Berguiga et al 32,33 Jegasothy et al, 34 also reported beneficial effects (wrinkle depth reduction, improved skin hydration, firmness and elasticity) of low molecular nano-hyaluronic acid injections. Positive changes in the appearance of the facial skin after HA treatment (improved firmness and pigmentation) were observed by Landi et al 35 Trong et al 36 also documented improved skin elasticity and wrinkle depth reduction, while Baspeyras et al, 37 observed significant improvement in skin hydration, firmness and viscoelasticity after HA microinjection treatment. A statistically significantly improved radiance, pigmentation and hydration were observed by Sparavigna et al, 38 in the process of treating skin with symptoms of ageing and photoaging.…”
Section: Discussionmentioning
confidence: 84%
“…10 Biophysical measurements and colorimetry showed improvement in both superficial and deep skin hydration, erythema, PH of skin, and sebum produc tion. [1][2][3][6][7][8][9]11,12,14 Histological and ultrasound evaluation confirmed clinicopathological and biophysical improvements was confirmed to continue up to 3 months by some studies. [1][2][3][6][7][8][9]11,12,14 In contrast, four studies revealed no significant improvement in clinical or histological features of skin with different compounds of mesococktail.…”
Section: Treatment Characteristics and Injection Techniquesmentioning
confidence: 91%
“…[1][2][3][6][7][8][9]11,12,14 Histological and ultrasound evaluation confirmed clinicopathological and biophysical improvements was confirmed to continue up to 3 months by some studies. [1][2][3][6][7][8][9]11,12,14 In contrast, four studies revealed no significant improvement in clinical or histological features of skin with different compounds of mesococktail. Although electron microscopy showed neocollagenesis of smaller caliber collagen fibers, but the result was not statistically significant.…”
Section: Treatment Characteristics and Injection Techniquesmentioning
confidence: 91%
See 1 more Smart Citation